Fluid shear stress improves morphology, cytoskeleton architecture, viability, and regulates cytokine expression in a time‐dependent manner in MLO‐Y4 cells. (1st August 2018) - Yan, Zedong; Wang, Pan; Wu, Junjie; Feng, Xue; Cai, Jing; Zhai, Mingming; Li, Juan; Liu, Xiyu; Jiang, Maogang; Luo, Erping; Jing, Da
Abstract: The effects of load‐induced interstitial fluid shear stress (FSS) on instantaneous signaling response of osteocytes (e.g., calcium signaling) have been well documented. FSS can also initiate the release of many important messenger molecules of osteocytes (e.g., ATP and PGE2 ). However, the effects of FSS on cellular function and bone metabolism‐modulating cytokine expression of osteocytes have not been fully identified (some inconsistent/conflicting results have been documented). Herein, osteocyte‐like MLO‐Y4 cells were stimulated with 1 Pa, 2‐h FSS, and the effects of FSS on cellular morphology, cytoskeletal microstructure, biological activity, and gene and protein expression of important cytokines were investigated. SEM and cytoskeleton staining revealed that FSS induced well‐organized cytoskeleton and increased filopodia processes. The osteocytic viability was sustained and apoptosis was inhibited via flow cytometry. FSS promoted Wnt3a and β‐catenin gene and protein expression in 0‐, 3‐, and 6‐h (sample collection time post FSS) groups. The FSS‐stimulated cells in the 3‐h group exhibited more significant effects on the promotion of OCN and Cx43 and inhibition of DKK1 and SOST expression than the 0‐ and 6‐h groups. The 3‐h group with FSS stimulation also showed the most prominent effects on suppressing RANKL and RANKL/OPG gene and protein expression. This study revealed a direct regulatory effect of FSS on osteocytic morphology and apoptotic characteristics, and showed that osteocyte‐secreted bone metabolism‐modulating molecule expression was regulated by FSS in a time‐dependent manner. This study not only enriches our basic knowledge for understanding osteocytic mechanotransduction, but also provides important evidence for more scientific experimental design.